Korelasi Kadar Serum Nitric Oxide (NO) dengan Tipe dan Derajat Keparahan Psoriasis - Fiska Rosita; Bobby Febrianto; Ambar Aliwardani; Putti Fatiharani; Wibisono Nugraha; Muhammad Eko Irawanto; Nurrachmat Mulianto (MEDICINUS, 2021)
Psoriasis is a chronic, immune-mediated disorder that results from a polygenic predisposition. Nitric oxide (NO) has been considered as important factors in the pathogenesis of psoriasis. This study aims to determine the correlation of serum NO levels with the type and severity of psoriasis. This cross-sectional study was conducted from May to September 2018. Difference in the average of serum NO levels in psoriasis patients with control groups is analyzed using t-test. The Spearman correlation test was used to see the correlation of serum NO levels with type and severity of psoriasis measured by Psoriasis Area and Severity Index (PASI) score. There was significant difference between serum NO level in the control group compared to the group of psoriasis patients (p=0.037). Patient with generalized pustular psoriasis has the highest mean of NO level (59.07 µmol/L). There was no significant correlation between serum NO level with type (r=0.008, p=0.9710 and severity (r=0.157, p=0.486) of psoriasis. Nitric oxide levels are elevated in psoriasis patients, which indicate that oxidative stress plays an important role in the etiopathogenesis of psoriasis.